Taming the gobal financial cycle: Central banks and the sterilization of capital flows in the first era of globalization - Guillaume Bazot; Eric Monnet; Matthias Morys (IBF - Institut für Bank- und Finanzgeschichte, 2019)
Are central banks able to isolate their domestic economy by offsetting the effects of foreign capital flows? We provide an answer for the First Age of Globalization based on an exceptionally detailed and standardized database of monthly balance sheets of all central banks in the world (i.e. 21) over 1891-1913. Investigating the impact of a global interest rate shock on the exchange-rate, the interest rate and the central bank balance sheet, we find that not a single country played by the 'rules of the game.' Core countries fully sterilized capital flows, while peripheral countries also relied on convertibility restrictions to avoid reserve losses. In line with the predictions of the trilemma, the exchange rate absorbed the shock fully in countries off the gold standard (floating exchange rate): the central bank's ba - lance sheet and interest rate were not affected. In contrast, in the United States, a gold standard country without a central bank, the reaction of the money mar - ket rate was three times stronger than that of interest rates in countries with a central bank. Central banks' balance sheets stood as a buffer between domestic economy and global financial markets.
Keywords: N10; N20; E42; E50; F30; F44; 330